GRUPO DE ESTUDOS EM ROBOTICA EDUCACIONAL - Krein, Natália; Danielsson, Gabriel Henrique; Bentz, Felipe; Fonseca, Rafael; Ziembowicz, Eduardo; Enderle, Taciana Paula (Salão do Conhecimento, 2019)
Projeto de extensão do curso de Engenharia Elétrica